Impact of Glucose Loading on Variations in CD4+ and CD8+ T Cells in Japanese Participants with or without Type 2 Diabetes - Miya, Aika; Nakamura, Akinobu; Miyoshi, Hideaki; Takano, Yoshinari; Sunagoya, Kana; Hayasaka, Koji; Shimizu, Chikara; Terauchi, Yasuo; Atsumi, Tatsuya (Frontiers in Endocrinology, 2018)
Objective: The aim of this study was to examine the fluctuations in CD4+ T cells, CD8+ T cells, and natural CD4+CD25+FoxP3+T-regulatory (Treg) cells following an oral glucose tolerance test (OGTT) in participants with and those without type 2 diabetes. Methods: Nineteen Japanese participants with type 2 diabetes (DM group) and 21 participants without diabetes (non-DM group) were recruited and underwent a 75-g OGTT. The cell numbers of leucocytes, lymphocytes, and the T cell compartment, such as CD4+, CD8+, and Treg, were calculated for blood samples obtained after an overnight 12-h fast and during a 75-g OGTT at 60 and 120 min. Results: Before glucose loading, no differences in the cell numbers of leucocytes, lymphocytes, CD4+, CD8+, and Treg were observed between the DM group and the non-DM group. The proportion of CD8+ was significantly reduced, whereas the proportion of CD4+ was significantly increased, after 120 min of glucose loading in both groups. The proportion of Treg was not affected. Furthermore, a significant positive correlation was observed between the AUC0-120 min of CD8+ and the change in the free fatty acid level following the OGTT (ρ = 0.39, P < 0.05), but not that of glucose or insulin. Conclusions: The proportion of CD4+ T cells was increased and that of CD8+ T cells was reduced after glucose loading in both subjects with and without diabetes. These findings suggest that glucose loading dynamically affects the balance of the circulating T lymphocyte subset, regardless of glucose tolerance.